ΚΟΙΝΟΤΗΤΑ ΚΑΙ ΠΡΕΣΒΕΙΕΣ ΣΤΙΣ ΒΕΝΕΤΟΚΡΑΤΟΥΜΕΝΕΣ ΕΛΛΗΝΙΚΕΣ ΠΕΡΙΟΧΕΣ. ΟΨΕΙΣ ΤΩΝ ΘΕΣΜΩΝ ΚΟΙΝΩΝΙΚΗΣ ΜΕΡΙΜΝΑΣ - ΜΟΥΣΑΔΑΚΟΥ ΚΑΤΕΡΙΝΑ (Eoa kai Esperia, 2007)
The embassies of communities of Greek regions under Venetian rule werean institution of the Serenissima Republic of Saint Mark, via which the localsocieties communicated with Venice. In the frame of the research programPYTHAGORAS II, titled «Greek Communities and European World (13th-19th c). Patterns of self-administration, social organization, identities’formation», were chosen the embassies that were included in the work ofConstantinos Sathas, «Monuments of Greek History», and more specifically,those from the IV and V volumes. The registration of a total of 94 embassiesof the 15th and 16th century from various Greek regions under Venetian rule,excluding Crete, and the presentation of short summaries of the content ofdemands and answers, in the data base that was created, offer information forthe study of a wide thematic field of Venetian and Greek history. As an example of using the data base, this article describes aspects ofinstitutions of social concern, focusing on the demands that were related tocereal supply policy, education and medical care. The requests of communities for the construction of barns and the missionof money for the supply of cereals reveal the vital problems of provisioningaccording to community and time. From another angle, the insistent demandsof communities for the employment of schoolteachers and for their paymentfrom Venice provide clues about the educational activities of Hellenism underVenetian rule. We also draw information about medical care as thecommunities asked from the Metropolis a community doctor and hisfinancing from Venice. The examination of these three aspects of social policy reveals to us thecontinuous efforts of local communities for the organization of a network ofsocial benefits, as well as the correspondence of Venice, positive or negative,in accordance always with the various economic, political and social factors ofeach time and place. Care for the different institutions of social concern appeared particularly important, to the extent that it served the catholicconcern of the Serenissima Republic of Saint Mark for the maintenance of hersocial status.